Does the timing of treatment with intraaortic balloon pump in cardiac surgery affect survival? - Amin Bagheri; Behrooz Banivaheb; Matineh Heidari; Jamshid Bagheri (Research in Cardiovascular Medicine, 2022)
Background: The intraaortic balloon pump (IABP) is the most common mechanical assist device used as an adjunctive therapy for patients with low cardiac output among cardiac surgery. However, controversy still exists about the optimal time for IABP insertion. The study evaluated the association between timing of IABP insertion and outcome in cardiac surgical patients. Patients and Methods: Patients who underwent cardiac surgery between August 2007 and June 2014 were included. 273 of 3480 patients (7.84%) required perioperative IABP support. Of whom 21 (7.7%) received a preoperative IABP, 180 (65.9%) received an intraoperative IABP and 72 (26.4%) received a postoperative IABP. Predictors of early mortality were measured in stepwise multivariate logistic regression analyses. Results: The overall mortality rate for all patients requiring IABP was 29.3%. The incidence of mortality in patients who underwent pre-, intra- and postoperative IABP insertion was 19.0%, 22.8%, and 48.6%, respectively. The independent predictors of early mortality were age, cross clamp time, and postoperative IABP. However, either pre or intraoperative IABP insertion was not associated with increase in early mortality. Conclusions: IABP treatment in patients undergoing cardiac surgery was relatively safe accompanied by few complications. Timing of IABP insertion appears to be associated with survival as early insertion results are much more desirable compared to postoperative insertion.